Endogeneity of Currency Areas and Trade Blocs: Evidence from the Inter-War Period - Nikolaus Wolf; Albrecht Ritschl (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2003)
Empirical research on the gravity model of international trade in the wake of Rose (2000) affirms that currency union formation doubles or triples trade. However, currency unions could also be established precisely because trade among their members was already high. In OLS estimation, this would cause endogeneity bias. The present paper employs both fixed effects and binary choice methods to trace endogeneity in the formation of historical currency arrangements. Studying the formation of currency blocs in the 1930s, we find strong evidence of endogeneity. We work with country group fixed effects and find that already in the 1920s, trade within the later currency blocs was up to three times higher than on average. The formal establishment of these blocs had only insignificant or even negative effects on the coefficients. We also employ a probit approach to predict membership in these later arrangements on the basis of data from the 1920s. Results are remarkably robust and again indicate strong self-selection bias. Evaluated against the control groups, treatment effects in the 1930s were mostly absent. Even the post-war currency arrangements are visible in the inter-war data. In line with the theory of optimum currency areas, our results caution against optimism about trade creation by currency unions.
Keywords: F33; F15; N70; 330; Currency blocs; gravity model; endogeneity; treatment effects